Multifunctional Nanoprobes From Design Validation to Biomedical Applications - Liu, Yanlan (Springer Theses, Recognizing Outstanding Ph.D. Research,, 2018)
This thesis mainly focuses on the design and synthesis of novel multifunctional nanoprobes, investigating their feasibility for applications involving sensing, molecular imaging, and the simultaneous diagnosis and therapy of cancer. Above all, it discusses the development of innovative nanomaterials to address the issues limiting the effectiveness of currently available nanoprobes such as the synthesis shortcoming and poor performance in sensing, imaging and therapeutic applications. One of the strengths of this thesis is its integration of knowledge from chemistry, materials science and biomedicine. Further, it presents the theoretical fundamentals in the design of nanoprobes, which can offer guidance for future studies on the development of novel multifunctional nanomaterials with significantly enhanced performance.